Global Phosphorus Enrichment Reshapes Terrestrial Phosphorus Cycling - Zixin Chen; Kai Dong; Julian Helfenstein; Dafeng Hui; Constantin M. Zohner; Frank Hagedorn; Manuel Delgado‐Baquerizo; Adam R. Martin; Jiguang Feng; Nan Yang; Xinli Chen; Laurent Augusto; et al. (Global Change Biology, 2026)
Anthropogenic phosphorus (P) inputs are rapidly altering terrestrial P cycling through plant – soil – microbial interactions; however, global patterns and underlying mechanisms driving these changes remain poorly understood. By performing a global meta‐analysis of 1315 observations from 176 studies across diverse natural terrestrial ecosystems, we found that P addition increased P concentrations in foliage, stems, roots, and litter by 62%, 114%, 100% and 63%, respectively. Soil total P, plant‐available P, and microbial P concentrations rose by 43%, 221%, and 70%, while leaf P‐resorption efficiency and soil phosphatase activity declined by 23% and 15%, respectively. Stem P and soil phosphatase activity exhibited consistent trends across tropical, temperate, and boreal zones, suggesting climate‐specific P acquisition strategies. In addition, foliar P responses diverged among ecosystem and plant functional types. These responses were primarily regulated by background soil total P concentration, precipitation, soil pH, and P addition duration and rate. Our findings provide critical insights into the potential consequences of increasing anthropogenic P inputs in natural terrestrial ecosystems, improving our understanding of nutrient cycling and informing future ecosystem management under ongoing global change.